1987
DOI: 10.1116/1.574496
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen contamination on the deposition of hydrogenated amorphous silicon films by tetrode radio frequency sputtering

Abstract: Electrical characterization of radio frequency sputtered hydrogenated amorphous silicon carbide films Structural and electrical studies of radio frequency sputtered hydrogenated amorphous silicon carbide films Stable hydrogenated amorphous silicon films deposited from silane and dichlorosilane by radio frequency plasma chemical vapor deposition Hydrogenated amorphous silicon films were deposited using the tetrode rf sputtering method by changing the hydrogen partial pressure ratio 5 to argon in atomospheric ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Some crystals were vertically grown, which were also composed of layer-structured crystal plates. In Al (20), it was clearly observed that most crystals were vertically grown (Fig. 1(d)).…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Some crystals were vertically grown, which were also composed of layer-structured crystal plates. In Al (20), it was clearly observed that most crystals were vertically grown (Fig. 1(d)).…”
Section: Resultsmentioning
confidence: 90%
“…1(d)). The average thickness of Al (15) and Al (20) was drastically increased compared with that of Al(0) and Al (10). This may be due to the rough surface of Al(0) and Al (10) and/or the perpendicular growth of crystals in Al (15) and Al (20).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations